(untitled) (Research, Society and Development, 2020)
The city of Rio de Janeiro presents several rocky outcrops, considered climbing sites, but presenting a characteristic, complex and sensitive flora. The present study aimed to survey flora and climber knowledge concerning the local vegetation in three Conservation Units in the city. A total of 44 species from 19 botanical families were identified by our group in climbing and track trails. As climbers are important users of these routes, 60 responded questionnaires to identify the possible presence of botanical blindness. Over 90% of the interviewed climbers understood the importance of conservation units and see the plants surrounding the trails, but were unable to identify most species. Therefore, plant blindness was identified, despite climber respect for nature. In addition, gaps were noted concerning climbing course contents on Botany and Environment in the assessed protected areas.